1999
DOI: 10.1007/bf01635047
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the common trunk of the middle and left hepatic veins: application to liver transplantation

Abstract: An anastomosis between the common trunk of the middle and left hepatic veins of the receiver and the cranial portion of the inferior vena cava of the donor is one of the techniques for restoration of hepato-caval continuity in orthotopic liver transplantation. This technique avoids dissection of the retrohepatic vena cava and total caval clamping. The aim of this study was to define the feasibility of this technique by a morphologic and biometric study of the common trunk of the middle and left hepatic veins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
9

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 10 publications
3
15
0
9
Order By: Relevance
“…A common trunk formed by the left hepatic vein and MHV is found in 70% of patients, and an intimate relationship exists between the two in 100% of patients, even when they join the IVC independently. 17 It can be challenging to separate these structures, and aggressive attempts could leave the remnant without adequate outflow. Because these concerns have not yet been realized in practice does not mean they are theoretical.…”
Section: Discussionmentioning
confidence: 99%
“…A common trunk formed by the left hepatic vein and MHV is found in 70% of patients, and an intimate relationship exists between the two in 100% of patients, even when they join the IVC independently. 17 It can be challenging to separate these structures, and aggressive attempts could leave the remnant without adequate outflow. Because these concerns have not yet been realized in practice does not mean they are theoretical.…”
Section: Discussionmentioning
confidence: 99%
“…16,28,47,84 The midhepatic vein is undoubtedly beneficial for the RL graft, and the remnant left lobe is probably not hurt by its absence, but its intimate relationship with the left hepatic vein is dangerous. 98,99 The left hepatic vein could be injured during dissection or narrowed by the closure of the orifice of the midhepatic vein, leaving the remnant left lobe with compromised outflow. The midhepatic vein should remain with the left lobe.…”
Section: Right Lobe Living Donor Liver Transplantationmentioning
confidence: 99%
“…6 In the absence of IVC or when it continues with the azygos vein, the VHs have to pass through the CO on the diaphragm to reach the right atrium. 3,6,9 Reviewing the general characteristics of 13 (7 males, 6 females) fetuses with hepatic veins opening into the IVC above the diaphragm showed that gestational ages of the fetuses ranged between 21 to 40 weeks. To the best of our knowledge, there are no publications in the literature that investigated these variations in the fetal period.…”
Section: Resultsmentioning
confidence: 99%